A content analysis of thinspiration images and text posts on Tumblr. (March 2018) - Wick, Madeline R.; Harriger, Jennifer A.
Highlights: Images typically included a thin woman adhering to culturally based beauty ideals About a third of the images were sexually objectifying Sexually objectifying text was rare Text posts contained guilt inducing messages about bodies and food Text posts encouraged restrictive dieting as a means of weight loss Abstract: Thinspiration is content advocating extreme weight loss by means of images and/or text posts. While past content analyses have examined thinspiration content on social media and other websites, no research to date has examined thinspiration content on Tumblr. Over the course of a week, 222 images and text posts were collected after entering the keyword 'thinspiration' into the Tumblr search bar. These images were then rated on a variety of characteristics. The majority of thinspiration images included a thin woman adhering to culturally based beauty, often posing in a manner that accentuated her thinness or sexuality. The most common themes for thinspiration text posts included dieting/restraint, weight loss, food guilt, and body guilt. The thinspiration content on Tumblr appears to be consistent with that on other mediums. Future research should utilize experimental methods to examine the potential effects of consuming thinspiration content on Tumblr.